Choosing best components for an amputee: a methodology for the best decision-making - Matos, José Pedro (2015)
The harmony between the stump and the prosthesis is critical to allow it to fulfill its function enabling an efficient gait. A well fitted socket, with an efficient and comfortable suspension, allows the amputee to continue their daily living activities, maintaining the stump functional, making this correlation between socket and suspension very important in the functionality of the prosthesis, mobility and overall satisfaction with the device. Of our knowledge, the quantitative correlation between all of these factors as not yet been assessed. Aim of study: Verify and confirm the process of decision-making for four different trans-tibial prostheses with suspension systems: Hypobaric(A), PIN(B), Classic Suction(C) and Vacuum Active –VASS(D) according data provided by gait efficiency (mlO2/kg/m) imagiology (pistonning) and amputee perception.